Linear Algebra – Why adj(A)A = det(A) * I

determinantlinear algebra

This is a statement in linear algebra that I can't seem to understand the proof behind.

For a square matrix $A$, why is:
$$\mathrm{adj}(A)A = \det(A) \cdot I$$

Any explanation would be greatly appreciated.

Best Answer

There is a nice short explanation. You probably know that the determinant of any matrix can be expanded row or column-wise using the minors:

$$\det A=\sum_{i=1}^n a_{ij}(-1)^{i+j}\det A(i\mid j)$$

or

$$\det A=\sum_{j=1}^n a_{ij}(-1)^{i+j}\det A(i\mid j)$$

for any $j$ (resp. $i$) or your liking where we obtain $A(i\mid j)$ by striking out the $i$-th row and the $j$-th column.

We define the coefficients of the adjoint $\hat A$ by $$(\hat A)_{ij}=(-1)^{{i+j}}\det A(j\mid i)$$

Now, upon matrix multiplication, we have

$$(A\cdot\hat A)_{k\ell}=\sum_{i=1}^n (-1)^{i+\ell}a_{ki} \det A(\ell\mid i)$$

If $k=\ell$, then $$(A\cdot \hat A)_{\ell\ell}=\sum_{i=1}^n(-1)^{i+\ell}a_{\ell i}\det A(\ell \mid i)=\det A$$ since we're expanding the determinant through the $\ell$-th row.

If $k\neq \ell$

$$(A\cdot\hat A)_{k\ell}=\sum_{i=1}^n (-1)^{i+\ell}a_{ki} \det A(\ell\mid i)=0$$

for it is the expansion of the determinant of the matrix $A^{k\ell}$ defined by $$(A^{k\ell})=\begin{cases} a_{ij} \text{ if }i\neq \ell\\a_{kj}\text{ if }i=\ell\end{cases}$$ which has two equal rows.